Development of Enteric-coated Tablets of Sodium 4,4'-(propnadiamido)dibenzoate - Ju. M. Kotsur; E. V. Flisyuk; I. A. Narcevich (Разработка и регистрация лекарственных средств, 2022)
Introduction. Enteric coat have a wide range of functions: from protecting the API from the adverse effects of the acidic environment of the stomach to targeted delivery to certain parts of the intestine in order to increase the effectiveness of the drug. When developing such dosage forms, special attention is paid to the type of film-forming polymer in the coating composition, its solubility and ability to withstand passage through the stomach.Aim. Development of enteric-coated tablets based on sodium 4,4'-(prpoandiamido)dibenzoate.Materials and methods. The objects of the study were sodium 4,4'-(propanediamido)dibenzoate 60 mg core tablets and compositions for enteric coatings. The uniformity of distribution of coatings over tablets was determined by the method developed at the Department of Technology of Medicinal Forms of SPCPU on the basis of the Fokker–Planck equation. The dissolution kinetics of enteric-coated tablets was studied using an Erweka DT 626 tablet dissolution tester (ERWEKA GmbH, Germany). The amount of the substance that passed into the dissolution medium was determined using an SF-2000 spectrophotometer (LLC "OKB Spektr", Russia).Results and discussion. It has been established that all the studied coatings are evenly distributed over the tablets. When studying the kinetics of tablet dissolution, it was found that all coatings are resistant to acidic environments (0.1 M hydrochloric acid solution), however, in a phosphate buffer solution, the highest rate of release of the substance from tablets is achieved using a coating based on a copolymer of methacrylic acid and ethyl acrylate of the type B.Conclusion. Tablets based on sodium 4,4'-(propanediamido)dibenzoate, enteric-coated AquaPolish® P white 712.06E were developed.